ANALISIS LAPORAN ARUS KAS SEBAGAI ALAT EVALUASI KINERJA KEUANGAN PADA PT. ACSET INDONUSA TBK TAHUN 2018-2022 - Halawa, Kristiani (Universitas Nias Raya, 2025)
Objective study This is For know how performance finance based on evaluation report current cash at PT. Acset Indonusa Tbk 2018-2022. Type aresearch used is study aqualitative with approach adescriptive. Internal data sources study This is report finances that have been published by PT. Acset Indonusa Tbk 2018-2022. Technique analysis of the data used is analysis ratio report current cash. Results research obtained based on analysis ratio report current cash show performance financing PT. Acset Indonusa Tbk 2018-2022 less Good. Based on ratio current cash operation to obligation fluent show that PT. Acset Indonusa Tbk from 2018-2022 no capable pay off obligation smoothly, based on ratio current cash operation to flower show that only on in 2020 and in 2021 PT. Acset Indonusa Tbk capable cover cost flower on debt that has been there is, based on ratio current cash operation to capital expenditure shows that only on in 2020 and in 2021 PT. Acset